Positions on sexual and reproductive rights in Muslim-majority countries and institutions: a telling indication of things to come?. Issue 5 (4th July 2017) - Karam, Azza
ABSTRACT: This article provides a policy analysis of Muslim-majority countries' positions on sexual and reproductive rights (SRR). First-hand observations, interviews, and reports are used to review how statements around various intergovernmental moments continue to be formulated since the International Conference on Population and Development in 1994. The analysis outlines both the similarity and diversity between and among Muslim-majority countries on a range of SRR areas, while pointing out that positions are by no means unique to them. Rather, it is argued that opposition to SRR defines a terrain of "unholy alliances" between and among different religiously inspired nations, and ends by enquiring whether SRR may be an important political indicator of real politik .